Membangun Aceh Melalui Pendidikan (Studi Analisis Konsep KOPELMA Darussalam Ali Hasjmy) - M. Adil (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2019)
This study aimed to investigate the background of the establishment of KOPELMA Darussalam, the concept of KOPELMA Darussalam proposed by Ali Hasjmy, and the relevance of Ali Hasjmy's educational thoughts with Aceh’s development through education. The study used a library research design, employing the primary data from Ali Hasjmy’s writings and the secondary data from two figures who had lived with and were close to Ali Hasjmy. The data were analyzed by using a descriptive analysis method. The results of the study revealed that Ali Hasjmy founded KOPELMA Darussalam as a manifestation of his educational, cultural, and political thoughts. This, in turn, gave birth to a big concept to Aceh’s development towards modernization, equipped with Islamic sharia, Acehnese culture and traditions, and science, after Aceh was hit by prolonged social conflict. The concept of KOPELMA Darussalam proposed by Ali Hasjmy intended to create KOPELMA Darussalam as a symbol of peace and love, a place to produce faithful and devoted humans to the religion and the nation, a place to establish science for humanity, a place to build